Multicenter, multinational, prospective cohort study of the impact of chlorhexidine impregnated versus plain central lines on central line-associated bloodstream infections - Rosenthal, Victor Daniel; Yin, Ruijie; Jin, Zhilin; Mat Nor, Mohd Basri; Lai, Yin Hoong; Mohamad, Fatimah; El-Kholy, Amani; Bayani, Victor; Hatem, Rana; Myatra, Sheila Nainan; Páez, Linda Castro; Kharbanda, Mohit; et al. (Elsevier, 2025)
Background: We compared the efficacy of chlorhexidine-impregnated central lines (CLs) with plain CLs in preventing central line-associated bloodstream infections (CLABSIs) in critically ill patients. Methods: The study was conducted from April 2023 to August 2024 in 8 hospitals across India, Malaysia, Papua New Guinea, Colombia, Egypt, and Turkey. Data were collected prospectively using the INICC Surveillance Online System. Cases and controls were recruited simultaneously. Data were analyzed using t tests, χ² tests, and Fisher exact tests when indicated. Relative risks (RR) and their corresponding 95% confidence intervals (CI) were calculated. Results: A total of 6,672 patients were included. Patients with impregnated CLs had 4,721 CL-days, while those with plain CLs had 18,822 CL-days. The CLABSI rate in patients with impregnated CLs was 1.48 per 1,000 CL-days, compared to 4.78 per 1,000 CL-days in those with plain CLs (RR=0.31, 95%CI =0.14-0.67, P= .003). A subgroup analysis excluding patients with hemodialysis but using central venous catheters (CVCs) showed 1.72 CLABSIs per 1,000 CL-days in patients with impregnated CVCs compared to 5.84 per 1,000 CL-days in those with plain CVCs (RR=0.29, 95%CI =0.12-0.68, P= .004). Conclusions: This study highlights the significant benefits of impregnated CLs over plain CLs in reducing CLABSI rates, achieving a 69% decrease in incidence.